Specific guidelines for assessing and improving the methodological quality of economic evaluations of newborn screening - Langer Astrid; Holle Rolf; John Jürgen (BMC, 2012)
Abstract Background Economic evaluation of newborn screening poses specific methodological challenges. Amongst others, these challenges refer to the use of quality adjusted life years (QALYs) in newborns, and which costs and outcomes need to be considered in a full evaluation of newborn screening programmes. Because of the increasing scale and scope of such programmes, a better understanding of the methods of high-quality economic evaluations may be crucial for both producers/authors and consumers/reviewers of newborn screening-related economic evaluations. The aim of this study was therefore to develop specific guidelines designed to assess and improve the methodological quality of economic evaluations in newborn screening. Methods To develop the guidelines, existing guidelines for assessing the quality of economic evaluations were identified through a literature search, and were reviewed and consolidated using a deductive iterative approach. In a subsequent test phase, these guidelines were applied to various economic evaluations which acted as case studies. Results The guidelines for assessing and improving the methodological quality of economic evaluations in newborn screening are organized into 11 categories: "bibliographic details", "study question and design", "modelling", "health outcomes", "costs", "discounting", "presentation of results", "sensitivity analyses", "discussion", "conclusions", and "commentary". Conclusions The application of the guidelines highlights important issues regarding newborn screening-related economic evaluations, and underscores the need for such issues to be afforded greater consideration in future economic evaluations. The variety in methodological quality detected by this study reveals the need for specific guidelines on the appropriate methods for conducting sound economic evaluations in newborn screening.